Composition Studies and Literary Criticism: A Hermeneutic Transaction - El Omari, Laila M. (Journal of English Language and Literature (ISSN: 2368-2132), 2017)
This paper presents a hermeneutic reading (from a Gadamerian perspective) of the complex relationships that tied the two fields of Composition Studies and Literary Criticism within the English department and across the academia. These two academic disciplines have remained in a dynamic, interactive, reciprocal relation throughout the decades. The paper surveys the published scholarship in the field of Composition Studies and presents a reading of the different themes, philosophies, and approaches that have kept the two fields in an interactive, dialogic process of formation. Terms and concepts from philosophical hermeneutics are introduced and employed to explain this relation.